SAT0323 MYOSITIS-SPECIFIC AND MYOSITIS-ASSOCIATED AUTOANTIBODIES IN A LARGE INDIAN COHORT OF INFLAMMATORY MYOSITIS REVEAL NOVEL CLINICO-PHENOTYPIC PATTERNS. (2nd June 2020) - Gupta, L.; Gaur, P.; Agarwal, V.; Aggarwal, R.; Misra, R.
Abstract : Background: Idiopathic Inflammatory Myositis (IIM) are heterogenous, with distinct autoantibodies reflecting upon possible clinical evolution and outcomes. Ethnicity has major influence on both antibody prevalence patterns as well as phenotypic behaviours linked to them. Objectives: Thus we sought prevalence and co-existence of myositis specific autoantibodies (MSAs) and myositis associated autoantibodies (MAAs) and associated clinical characteristics in a large cohort of patients with IIM. Methods: Adult patients with a physician diagnosis of IIM as per ACR/EULAR classification criteria were investigated for the presence of MSAs/MAAs by Line immunoassay (G4, Euro-Immune, Lubeck, Germany). Anti-Nuclear Antibody (ANA) was tested by Immunofluorescence assay (IFA), and patterns in various antibody subsets explored. Prevalence and associations of different antibodies were assessed in disease subsets and clinical phenotypes. Results: MSA and MAAs were tested in 250 IIM patients (F:M 3.8:1) of median age 37 (25-47) and disease duration 6 (3-17) years. Dermatomyositis (DM) was seen in most patients 83 (33.2%) followed by overlap myositis (OM), juvenile DM, Anti-synthetase syndrome (ASS), polymyositis (PM), and cancer associated myositis (CAM). MSAs/MAAs were found in 148 (59.2%) of patients, of which 95 (64.2%) had an MSA and 53 (35.8%) had MAAs (Fig, 1A ). 93 (62.8%) of autoantibody positive patients were positive for a single antibody, and only 2 (0.8%) of total had more than one MSA (Table 1 ). Note: ** PL-7 co-exists with Ku + Pm/Scl, **PL-12 co-exists with Pm/Scl + Ro52, **SRP co-exists with Pm/Scl + Ro52 The most frequently detected MSA was anti-Jo-1 (8%), with a further 9 specificities each found in 0.5–7.0% of patients. Amongst the autoantibody positive patients, 21% (n=53) had isolated MAA positivity, anti-Ro52 (33, 62.3%) being the most common, followed by anti-Pm/Scl (11, 20.8%) and anti-Ku (9, 17.0%) (Fig. 1B ). On ANA, 76.0% (172 of 226) were positive, with speckled being the most common pattern (37%, Fig. 1C ). Of those ANA negative (n=54), 61% had either MSA or MAA (Fig 1D ). 18 (54.6%) had autoantibodies associated with cytoplasmic patterns suggesting that cytoplasmic ANA may be underreported. Clinical presentation akin to DM was seen with all MSA except anti-SRP. PM group was heterogenous, and included ASS, OM and necrotizing phenotype (Fig. 2A ). On occasion, anti-SRP, anti-Mi-2 and anti-MDA5 presented with clinical phenotype of ASS. (Fig 2 A, C ). Patients with ARS or anti-SAE were often clinically amyopathic (Figure 2 B, C ) ARS were associated with mechanic's hand (p<0.0001, OR 7.6), ILD (p<0.0001, OR 4.4), and arthritis (p=.002, OR 2.6) though there was no difference between Jo-1 and non-Jo-1 ASS. Anti-MDA-5 associated with fever (p=0.003, OR 12) and weight loss (p=0.008, OR 10.2) and unique phenotype of eye-lid edema in some adults (Figure 2 E ) and arthritis in children (p=0.01, OR 11.5). Anti-TIF-1ɣ associated with alopecia (p=0.007, OR 5.9) and malignancy (p= <0.0001, OR 34) in adults but not children. Conclusion: Myositis autoantibodies are seen in two-thirds IIM and identify distinct clinical subsets as well as unique phenotypes. MSA/MAA are positive in two-thirds of those negative on ANA, adding diagnostic value. MSAs are nearly always mutually exclusive and thus useful as biomarkers for diagnosis. Acknowledgments: MSA testing supported by grants from APLAR and Association of Physicians of India. Disclosure of Interests: Latika Gupta: None declared, Priyanka Gaur: None declared, Vikas Agarwal: None declared, Rohit Aggarwal Grant/research support from: Pfizer, Genentech, BMS, Mallinckrodt, Consultant of: Pfizer, Genentech, BMS, Mallinckrodt, Bristol Myers-Squibb, octapharma, CSL Behring, AstraZeneca, Corbus, Kezar, Abbvie, Ramnath Misra: None declared